Computed tomographic features of the feline brain change with advancing age? - Babicsak, Viviam R. [UNESP]; Cardoso, Guilherme S.; Tsunemi, Miriam H. [UNESP]; Vulcano, Luiz C. [UNESP] (FapUNIFESP (SciELO), 2015)
A better understanding of normal or expected encephalic changes with increasing age in cats is needed as a growing number of these animals is attended in veterinary clinics, and imaging data referring to normal age-associated changes are extremely scarce in the literature. The objective of this study was to identify age-related changes in feline brain using CT imaging. Fifteen non-brachycephalic healthy cats with age between 1 to 6 years (adult group) and others over 12 years (geriatric group) were submitted to CT scan of the brain. Statistically significant differences were found between the groups for the ability to identify the left lateral ventricle and for falx cerebri calcification, both identified in a greater number of cats of the geriatric group. A significantly higher mean width of the third ventricle was also detected in geriatric animals. There were no statistically significant differences between lateral ventricular dimensions and encephalic parenchymal attenuation on pre and post-contrast CT phases. The results of the present study show an increase in the incidence of falx cerebri calcification and a third ventricular dilatation with advancing age in cats. Future researches using MRI scanners and a greater quantity of cats are needed in order to identify supplementary age-related changes.
Keywords: Cat; Cerebral aging; Computed tomographic imaging; Neuroanatomy